Corrosive wear characteristics of bronze friction resisting composites. (March 2013) - Ragab, Kh A; Abdel-Karim, R; Bournane, M; Farag, S; El-Raghy, S M; Ahmed, H A
<x content-type="archive" xml:space="preserve">Abstract</x> Three groups of bronze based composites with different amounts of slide additive (graphite) and friction additives (SiC and SiO2) were prepared by powder metallurgy technique. The corrosive wear behaviours of the resulting composites in electrochemical aqueous solutions, namely, acidic rain, neutral rain and wastewater, were comparatively investigated. The corrosive wear mechanisms of the bronze composites were discussed based on examination of the worn surface morphologies of the composite block materials by means of scanning electron microscopy equipped with an energy dispersion spectrometry. The determination of corrosive wear rates was carried out by means of a combination of electrochemical and gravimetric techniques. Increasing both slide and friction additives improved the corrosion resistance of these bronze composites. Samples with 1·5% graphite, 3%SiO2 and 3%SiC had the highest corrosive wear resistance in neutralised as well as in acid rain due to the high amount of antifriction and slide additives, in addition to low porosity.